2021
DOI: 10.1177/15533506211037792
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Assessment of Knee Arthroscopy Skills Between Medical Students and Residents—Simulator Exercises for Partial Meniscectomy and Analysis of Learning Curves

Abstract: Background The Covid-19 pandemic has created the largest disruption of education in history. In a response to this, we aimed to evaluate the knee arthroscopy learning curve among medical students and orthopaedic residents. Methods An arthroscopy simulator was used to compare the learning curves of two groups. Medical students with any prior knowledge of arthroscopy ( n=24) were compared to a residents group ( n=16). Analyzed parameters were “time to complete a task,” assessment of the movement of tools and val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Furthermore, 1 study even found VR simulation to be as effective as cadaver training, and residents rated VR education as comparable in effectiveness to surgical experiences, although further research is required to determine the applicability and usage of VR 86 . By contrast, more traditional physical surgical simulators showed learner improvement in arthroscopy skills 87 . Other technologies such as 3D-printed lumbar spines showed feasibility to practice pedicle screw placement in an affordable and remote manner 88 .…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Furthermore, 1 study even found VR simulation to be as effective as cadaver training, and residents rated VR education as comparable in effectiveness to surgical experiences, although further research is required to determine the applicability and usage of VR 86 . By contrast, more traditional physical surgical simulators showed learner improvement in arthroscopy skills 87 . Other technologies such as 3D-printed lumbar spines showed feasibility to practice pedicle screw placement in an affordable and remote manner 88 .…”
Section: Resultsmentioning
confidence: 85%
“…These findings suggest a balance may need to be struck between inperson and online education. Finally, the utility of VR and simulations was recognized and accelerated as a result of the pandemic for socially distanced surgical training; future directions will focus on augmenting long-term skill retention and transferability [85][86][87]90 . By providing a safe, controlled, and customizable environment for skill development, these technologies can accelerate learning, promote interdisciplinary collaboration, and improve overall surgical competence, ultimately benefiting both trainees and patients.…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed that blinded graders from other institutions are best for grading maximum depth applied to damageable tissues by a tool in the simulation. Although tool-distance-traveled metrics differentiated between trainees with different skill levels performing diagnostic knee arthroscopy, loose body retrievals, and partial meniscectomies on a virtual reality arthroscopy simulator [17,18,72], the roughness parameter was not different between trainees with different experience levels [17,72]. In other studies, neither tool distance traveled nor damage to tissues were reliable metrics in differentiating users by experience level during diagnostic virtual reality hip arthroscopy and loose body removal [13], as well as during virtual reality arthroscopic ACL reconstruction [7].…”
Section: Surgical Tasks Other Than Arthroscopymentioning
confidence: 99%
“…After full-text review, we included 27 studies investigating the use of film review in orthopaedics including five randomized controlled trials [8, 9, 21, 36, 47] and 22 observational studies [3, 11, 12, 15, 20, 23, 24, 30, 41, 44, 50-52, 56, 61, 64, 65, 69, 77, 78, 81, 82]. We included 28 studies investigating the use of motion analysis in orthopaedics, including four randomized controlled trials [40, 58, 62, 70] and 24 observational studies [2, 7, 13, 14, 17, 18, 32, 38, 39, 43, 49, 57, 63, 67, 68, 71-73, 75, 76, 83, 84, 89, 90].…”
Section: Essential Elementsmentioning
confidence: 99%
“…Arthroscopic methods are rapidly developing, and residents are being required to master increasingly complex surgical skills in a shorter period [2]. Thus, it is important to consider the steep learning curve of this specialty [16][17][18][19][20][21]. In recent years, simulation training has been used in other surgical areas, and studies have shown that practising surgical skills using a proven simulator can effectively shorten the learning curve [20].…”
Section: Introductionmentioning
confidence: 99%